Natriuretic peptides and their therapeutic potential in heart failure treatment: An updated review - Namdari, M; Eatemadi, A; Negahdari, B (Cellular and Molecular Biology, 2016)
Brain natriuretic peptide (BNP), also known as a B-type natriuretic peptide, is one of the important biomarkers with a proven role in the diagnosis of congestive heart failure (CHF). Researchers from the different clinical field have researched into the performance features of BNP testing in the acute care set-up to assist and improve in diagnosing CHF and in predicting future morbidity and mortality rates. The potency of BNP has also been researched into in cases like myocardial ischemia and infarction, cor pulmonale, and acute pulmonary embolism (PE). Based on their vaso-dilatory and diuretic properties and ability to inhibit renin–angiotensin–aldosterone system, natriuretic peptides are able to provide an efficient technique and mechanism of action in the pathophysiologic framework for CHF treatment and management. Recent clinical studies reported that ularitide, a synthetic form of urodilatin, secreted by kidney may be effective in managing and treatment of decompensated heart failure. It has also been reported that Nesiritide, a recombinant natriuretic peptide has been proven to improve dyspnea and hemodynamic parameters in heart failure patients. This review provides an update on natriuretic peptides and their therapeutic potential in CHF treatment.